Breast mass segmentation in ultrasound with selective kernel U-Net convolutional neural network - Byra, Michal; Jarosik, Piotr; Szubert, Aleksandra; Galperin, Michael; Ojeda-Fournier, Haydee; Olson, Linda; O’Boyle, Mary; Comstock, Christopher; Andre, Michael (Biomedical signal processing and control, 2020)
•Convolutional neural networks can efficiently segment breast masses in ultrasound.•Segmentation network's receptive field can be adjusted with an attention mechanism.•Segmentation performance assessment based on multiple datasets. In this work, we propose a deep learning method for breast mass segmentation in ultrasound (US). Variations in breast mass size and image characteristics make the automatic segmentation difficult. To address this issue, we developed a selective kernel (SK) U-Net convolutional neural network. The aim of the SKs was to adjust network's receptive fields via an attention mechanism, and fuse feature maps extracted with dilated and conventional convolutions. The proposed method was developed and evaluated using US images collected from 882 breast masses. Moreover, we used three datasets of US images collected at different medical centers for testing (893 US images). On our test set of 150 US images, the SK-U-Net achieved mean Dice score of 0.826, and outperformed regular U-Net, Dice score of 0.778. When evaluated on three separate datasets, the proposed method yielded mean Dice scores ranging from 0.646 to 0.780. Additional fine-tuning of our better-performing model with data collected at different centers improved mean Dice scores by ∼6%. SK-U-Net utilized both dilated and regular convolutions to process US images. We found strong correlation, Spearman's rank coefficient of 0.7, between the utilization of dilated convolutions and breast mass size in the case of network's expansion path. Our study shows the usefulness of deep learning methods for breast mass segmentation. SK-U-Net implementation and pre-trained weights can be found at github.com/mbyr/bus_seg.